2020
DOI: 10.3389/fcell.2020.00543
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Virus Regulatory Insights Into Avian N6-Methyladenosine (m6A) Machinery

Abstract: The addition of a methyl group to the N6 position of adenosine (m6A) is the most common posttranscriptional RNA modification, and it regulates most steps of RNA metabolism including splicing, stability, translation, nuclear-export, and RNA structures. Besides cellular RNA, m6A modifications have also been detected on viral RNA. A range of recent studies have demonstrated the crucial roles of m6A in the virushost interactions; however, m6A cellular machineries are only characterized in limited mammalian species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…The epigenetic m 6 A mark is the most abundant internal chemical modification installed onto both cellular and viral mRNA that dictate various cell behaviours and the fate of the virus-host interaction 2 , 39 . The significance of m 6 A has been highlighted by the fact that this modification is evolutionarily conserved among vertebrates 31 , besides, a high degree of conservation in the majority of m6A machinery has recently been confirmed among vertebrates 9 . Furthermore, the overall inhibition of m 6 A has various detrimental effects on animals' life 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epigenetic m 6 A mark is the most abundant internal chemical modification installed onto both cellular and viral mRNA that dictate various cell behaviours and the fate of the virus-host interaction 2 , 39 . The significance of m 6 A has been highlighted by the fact that this modification is evolutionarily conserved among vertebrates 31 , besides, a high degree of conservation in the majority of m6A machinery has recently been confirmed among vertebrates 9 . Furthermore, the overall inhibition of m 6 A has various detrimental effects on animals' life 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the m 6 A marks on both cellular and viral RNA is governed by a complex group of nuclear methyltransferases (writers); these marks can be removed by another group of demethylases (erasers). Ultimately, a third group able to bind and generate a recognizable effect on the methylated transcripts (readers), all groups are collectively known as m 6 A machinery 9 , 25 27 . Installation of m 6 A is predominantly restricted to consensus sequence motif, the putative m 6 A sites significantly reported to be enriched in some 5′-DRA*CH-3′ sequences (where A* denotes the methylatable adenosine, D denotes A, G or U, R denotes A and G, and H denotes A, C or U) 24 , 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…A higher degree of conservation to the residues surrounding the methylated base in both H. sapiens and avian species was noticed, indicating a highly conserved catalytic mechanism even in various organisms exhibiting evolutionary changes. Moreover, we have found that the pincer-like structure in avian species suggests a higher binding affinity with more stabilizing property compared with H. sapiens (Bayoumi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our group has performed a recent comprehensive analysis of the m 6 A demethylases among various orders of animals, especially the avian species (Bayoumi et al, 2020 ). The study revealed multiple evolutionary changes when compared with Homo sapiens .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation